ANALISIS TINGKAT KEUNTUNGAN NELAYAN GILLNET ¾ INCHI (JARING WADER) DAN NELAYAN GILLNET 3 INCHI (JARING ARANG) DI PERAIRAN RAWAPENING DESA BEJALEN KECAMATAN AMBARAWA KABUPATEN SEMARANG - Wijayanti, Angga; -, Ismail; Fitri, Aristi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Profit is the quarrel of total revenue and total cost in the production process. In the Bejalen village there are 2 kinds gill nets are gill nets ¾ inch (net Wader) and a 3-inch gill nets (net arang).Differences of mesh size affect The catch, more high of cath can afford income higher. The purposes of this study were to identify differences kind of catch, profit difference between Wader nets and arang nets, analyze the income of fisherman compared to UMK Semarang district, identifying the technical and financial aspects at Wader nets and arang net .Descriptive method based on case studies used in this study. The sampling method used census. The method of analysis used were financial analysis and feasible study analysis. The results showed a net profit of Wader Rp2.298.345,10, arang nets profit Rp3.510.373,43, wader net income was Rp5.233.129,41, arang nets was Rp6,722,368.421. feasible study analysis showed R/C 1,8 wader net,PP one years NPV Rp804.732,5128, B/C 1.05, IRR of 19,21 . While R/C for arang net 2,2, PP seven month, NPV Rp7.026.351,44, B/C 1,52, IRR 29,00. Conclusion effort arang nets composition of catches more varied and have greater profits. Fisherman’s income were still under the UMK of Semarang district. From the financial analysis for both of fishing commerce were feasible to run.